Scald Injury-Induced T Cell Dysfunction Can Be Mitigated by Gr1+ Cell Depletion and Blockage of CD47/CD172a Signaling - Beckmann, Nadine; Huber, Franziska; Hanschen, Marc; St. Pierre Schneider, Barbara; Nomellini, Vanessa; Caldwell, Charles C. (Frontiers in Immunology, 2020)
Infection is a common and severe complication of burn injury: Sepsis accounts for 47 % of postburn mortality. Burn-induced T cell suppression likely contributes to the increased infection susceptibility in burn patients. However, little is known about the kinetics of T cell dysfunction after burn and its underlying mechanisms. In this study, we show in a murine scald injury model that T cell activation of both CD4+ and CD8+ T cells as well as T cell cytokine production is suppressed acutely and persistently for at least 11 days after burn injury. Purified T cells from scald-injured mice exhibit normal T cell functions, indicating an extrinsically mediated defect. We further show that T cell dysfunction after burn appears to be cell-to-cell contact dependent and can be ameliorated by depletion of myeloid-derived suppressor cells. These cells expand after burn injury, particularly a subset expressing the checkpoint inhibitor CD172a, and infiltrate germinal centers. Expression of CD172a appears to be driven by ingestion of immature reticulocytes. Immature reticulocytes are drastically increased in the spleen of scald mice and may contribute to immunosuppression through more direct mechanisms as well. Overall, our study newly identifies two cell populations, myeloid-derived suppressor cells and immature reticulocytes, as well as the CD47/CD172a-signaling pathways as mediators of T cell suppressors after burn and thus opens up new research opportunities in the search for new therapies to combat increased infection susceptibility and the associated morbidity and mortality in burn victims.